2012
DOI: 10.1016/j.chembiol.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase 3 Protects Beta Cells from Cytokine-Induced Apoptosis

Abstract: Summary Cytokine-induced beta-cell apoptosis is important to the etiology of type-1 diabetes. Although previous reports have shown that general inhibitors of histone deacetylase (HDAC) activity, such as suberoylanilide hydroxamic acid and trichostatin A, can partially prevent beta-cell death, they do not fully restore beta-cell function. To understand HDAC isoform selectivity in beta cells, we measured the cellular effects of eleven structurally diverse HDAC inhibitors on cytokine-induced apoptosis in the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 15 publications
(19 reference statements)
2
67
0
Order By: Relevance
“…Inhibition of HDACs has also been shown to have important functions in preventing β -cell inflammatory damage, improving insulin resistance, promoting β -cell development, proliferation, differentiation and function, and positively having an impact on late diabetic microvascular complications [121]. Both pharmacological and genetic inhibition of HDAC3 has been shown to protect β -cells against cytokine-induced apoptosis and restores glucose-stimulated insulin secretion [128]. In addition, oral administration of ITF2357, a class I and II HDACI, improved islet function, reduced iNOS (inducible NOS) levels and apoptosis [129].…”
Section: Hdacs and Metabolic Disordersmentioning
confidence: 99%
“…Inhibition of HDACs has also been shown to have important functions in preventing β -cell inflammatory damage, improving insulin resistance, promoting β -cell development, proliferation, differentiation and function, and positively having an impact on late diabetic microvascular complications [121]. Both pharmacological and genetic inhibition of HDAC3 has been shown to protect β -cells against cytokine-induced apoptosis and restores glucose-stimulated insulin secretion [128]. In addition, oral administration of ITF2357, a class I and II HDACI, improved islet function, reduced iNOS (inducible NOS) levels and apoptosis [129].…”
Section: Hdacs and Metabolic Disordersmentioning
confidence: 99%
“…Class I HDACs are ubiquitously expressed and have been implicated in regulation of metabolic gene signatures [7]. In the past several years, multiple studies of siRNA knockdown and pharmacological inhibition of HDAC3 have suggested a role for HDAC3 in β-cells, with loss of HDAC3 function protecting β-cells from cytokine-induced apoptosis and helping to maintain proper glucose-stimulated insulin secretion [8], [9], [10], [11], [12]. Furthermore, an HDAC3-specific inhibitor was reported to improve glucose homeostasis and insulin secretion in a diabetic rat model [11].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] CI-994 has also been pursued as a treatment for neurodegenerative diseases and for diseases outside of the brain. 36,37 For example, it was recently reported that CI-994 inhibition of HDACs may have potential as for the treatment of memory/cognition and anxiety disorders (Tsai, et al submitted) CI-994 is a class I HDACs inhibitor, selective for HDAC1, 2 and 3 with varying potency. 39 Thus, a tritium-labeled version could provide a map of HDAC1-3 and be used to associate this class with disease, to develop class B max of 13.6 picomol·mg −1 protein and K d 9.6 nM.…”
Section: Resultsmentioning
confidence: 99%